Maresin-2 alleviates allergic airway inflammation in mice by inhibiting the activation of NLRP3 inflammasome, Th2 type immune response and oxidative stress. (June 2022) - Yu, Cheng-xiu; Shi, Zu-an; Ou, Guo-chun; Chen, Xiao-ju; Liu, Qin; Zeng, Di; Nie, Xue-ju; Chen, Jian-jun
Abstract: Asthma is a chronic inflammatory disease of the respiratory system. Maresin-2 (MaR2) is biosynthesized from docosahexaenoic acid (DHA) by macrophages, display strong anti-inflammatory and pro-resolving activity. To investigate the therapeutic effect and mechanism of MaR2 on asthmatic mice induced by ovalbumin (OVA) in conjunction with the adjuvant aluminum hydroxide. Twenty four female BALB/c mice were randomly divided into control, OVA, OVA + MaR2, and OVA + dexamethasone (Dexa) groups. MaR2 or Dexa were given as a treatment for OVA-induced asthma. Serum, bronchoalveolar alveolar lavage fluid (BALF) and lung tissue were collected for further analysis. The Pathological changes of lung tissue, proportion of inflammatory cells in BALF, levels of inflammatory cytokines in BALF or serum, oxidative stress indices, and the protein concentration of ASC, MPO, Ly-6G, ICAM-1, NLRP3 and Caspase-1 in lung tissues were evaluated. Compared with the OVA group, both OVA + MaR2 and OVA + Dexa group had reduced inflammation and mucus secretion in lung tissue, number of inflammatory cells in BALF, levels of related inflammatory cytokines in serum or BALF, and expressions of ASC, MPO, Ly-6G, ICAM-1, NLRP3 and Caspase-1 proteins in lung tissue. In addition, the oxidative stress was alleviated as indicated by decreased MDA, and elevated SOD and GSH. MaR2 has an obvious protective effect on OVA-induced bronchial asthma in mice, in a similar manner as Dexa. The mechanism may be related to the inhibition of the Th2 type immune response, the NLRP3 inflammasome activation and oxidative stress. Highlights: MaR2 alleviate inflammatory cell infiltration and oxidative stress in OVA-induced asthma. The mechanism may be inhibiting the activation of NLRP3 inflammasome, Th2 type immune response and oxidative stress. MaR2 may be used as a potential drug for the treatment of asthma in the future.